PENGARUH KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN ULANG SABUN MANDI MEREK SHINZUI DI KOTA PALU - Hartati, Hartati (Fakultas Ekonomi Universitas Tadulako, 2017)
The purpose of this study is to determine simultaneous and partial influence of product quality both on repurchase decision of Shinzui bath soap in Palu City. Independent variables used in this study consist of performance, features, reliability, durability, conformance, aesthetics, and perceived quality; while dependent variable is repurchase decision (Y). The research method is descriptive. Sample consists of 80 respondents who selected by purposive sampling technique. Data analysis method is multiple linear regressions. The result of this research shows that product quality, consists of performance, feature, reliability, durability, conformance, aesthetics, and perceived quality simultaneously have significant influence on repurchase decision of Shinzui bath soap in Palu City. Partially, product qualities that consist of feature and perceived quality have significant influence on repurchase decision of Shinzui bath soap in Palu City. While performance, reliability, durability, conformance, and aesthetics variables partially have non-significant influence on repurchase decision of Shinzui bath soap in Palu City.